INTEGRASI ILMU DAN AGAMA DALAM PEMIKIRAN PENDIDIKAN ISLAM - Muhammad Jamaluddin; Zainal Abidin; Ali Maschan Moesa (CV. Jendela Gagasan, 2026)
The phenomenon of the dichotomy of science in Islamic education, which has its roots in colonialism and has been further reinforced by the tide of modernization, has given rise to an epistemological crisis that separates rationality from spirituality. This situation underscores the importance of rebuilding an integrative paradigm that places science and religion as two complementary dimensions in the process of civilization. This study aims to examine the concept of the integration of science and religion in Islamic educational thought, while emphasizing its relevance to social, cultural, and educational dynamics in the contemporary era. Using a qualitative approach in the form of a literature study, this research utilizes various sources such as academic documents, books, and scientific articles that are analyzed thematically to find patterns of meaning and theoretical contributions. Data collection was carried out through the stages of identification, search, selection, recording, and organization of literature, while data analysis was carried out by interpreting and reflecting on the themes that emerged from the literature review. The results of the study show that the integration of science and religion does not stop at the normative level but functions as a practical strategy to respond to the challenges of globalization, strengthen the character of Islamic education, and build a more comprehensive epistemological model.